PERLINDUNGAN HUKUM BAGI ANAK SEBAGAI KORBAN DALAM KASUS TINDAK PIDANA KEKERASAN SEKSUAL DI INDONESIA - Susiana Kifli (Collegium Studiosum Journal, 2025)
Violence against women is a crucial issue and a current challenge. Many cases of women becoming victims due to vulnerability and powerlessness. In fact, the tendency of victims being children is also increasing nowadays, both in the family, in the community, and in the school environment. Legislation in Indonesia, starting from the 1945 Constitution, the Criminal Code, the Child Protection Law, the Domestic Violence Law, to the TPKS Law, expressly guarantees protection for children from all forms of violence, including sexual violence. The type of research used in this paper is normative juridical legal research. However, the effectiveness of its implementation still faces various obstacles, such as limited human resources of law enforcement officers, a lack of understanding of regulations, minimal facilities and financial support, and the absence of special services for victims. In addition, the low level of Lack of public awareness and a culture of shame in reporting cases further exacerbate the situation. By identifying and addressing these challenges, it is hoped that the implementation of legal protection for child victims of sexual violence can be more effective and have a positive impact on victims and society as a whole. Solid collaboration between the government, child protection agencies, the police, the judicial system, and the community is needed to overcome these challenges and provide better protection for child victims of sexual violence.